Perceptual learning improves spatial contrast sensitivity in older adults - Tang, Yong; Liang, Ju; Zhou, Yifeng (Frontiers in Neuroscience, 2025)
IntroductionWidespread visual deficits accompany normal aging, with most attributed to functional degradation of the visual cortex. Although perceptual learning can improve many visual functions in older adults, it remains unclear whether it can enhance spatial contrast sensitivity, a fundamental visual function known to decline significantly from around age forty.MethodsTo address this, we trained 29 older adults and 18 young controls using contrast perceptual learning. Training was conducted at seven spatial frequencies (from low to high) and/or at the individual cut-off spatial frequency. Spatial contrast sensitivity function (SCSF) and visual acuity (VA) were measured before and after training.ResultsTraining induced substantial improvements in both SCSF and VA in older adults, which were retained for at least several months. Analysis of transfer effects revealed that, compared to young controls, older adults exhibited a characteristic low-frequency shift in peak improvement and a slightly broader bandwidth.DiscussionThese results may be associated with age-related alterations in neuronal response properties within the primary visual cortex. Our findings demonstrate substantial neural plasticity in the aging visual system and support the potential of perceptual learning as a clinically viable intervention for mitigating age-related visual decline.